2021
DOI: 10.1111/tbj.14259
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious breast lesions incidentally detected on chest computer tomography with histopathological correlation

Abstract: Several imaging techniques are available for the diagnosis of breast cancer. Mammography is the preferred screening method for breast cancer detection; however, incidental findings of the breast often present on multidetector computed tomography scans (CT), carried out for different reasons.A disadvantage of thoracic CT scans is the radiation exposure to the breast tissue. The effective dose during a thoracic CT scan is with 4-7 mSv significantly higher than the effective dose obtained during a conventional ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Finally, we compared the nodule characteristics on CT that we found to be predictive of breast cancer with those reported in the literature. From this comparison, it emerges that our results are in good agreement with those published by Lin et al [ 17 ] and Georgieva et al [ 18 ], while they differ from the findings by Prionas et al [ 16 ] and Moyle et al [ 19 ] (see Table 5 ). One of the major limitations to these studies lies in their retrospectivity, which also flaws our findings.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Finally, we compared the nodule characteristics on CT that we found to be predictive of breast cancer with those reported in the literature. From this comparison, it emerges that our results are in good agreement with those published by Lin et al [ 17 ] and Georgieva et al [ 18 ], while they differ from the findings by Prionas et al [ 16 ] and Moyle et al [ 19 ] (see Table 5 ). One of the major limitations to these studies lies in their retrospectivity, which also flaws our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Among the CT signs indicative of malignancy is post-contrast enhancement, which is predictive of both BIRADS-5 on subsequent mammography and cancer diagnosis on histopathological examination [ 16 18 ]. A further contribution can be given by the morphological analysis: the irregularities of the lesion margins were found to be predictive of both possible BI-RADS 5 classification on mammography and malignancy on histopathological examination [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern CT now has improved contrast resolution, a greater field of view, and a cross-sectional capability to characterize a mass in greater detail ( 8 ). A few studies reported there to be significant correlation between the CT presentation of breast images and histopathology, with CT being particularly useful in assessing suspicious changes in dense breast tissue ( 9 , 10 ). Currently, the National Comprehensive Cancer Network (NCCN) for breast cancer recommends CT or positron emission tomography- CT (PET/CT) imaging for patients with stage III to IV disease and chest CT for patients with early-stage disease and pulmonary symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the 3D nature of bCT has the potential to decrease false-negative exams in dense breast tissue where malignant lesions may be difficult to discern by removing the superimposition of benign and malignant breast tissue [ 39 44 ]. Studies have shown that detection rates for malignant masses are significantly improved at contrast-enhanced breast CT (CEbCT) than at mammography, tomosynthesis, or unenhanced breast CT [ 38 , 39 , 43 , 45 ]. The sensitivity, specificity, and accuracy of chest CT for breast cancer detection have been reported to be 84.21%, 99.3%, and 98.68% compared to 78.95%, 93.78%, and 93.16% for mammography [ 44 ].…”
Section: Introductionmentioning
confidence: 99%